(untitled) (Vietnam Journal of Community Medicine, 2025)
Research on the current status of human resources at health stations of Luc Nam Dist Health Center, Bac Giang Province, period 2021-2022. Cross-sectional descriptive design combining qualitative and quantitative. The research subjects are medical staff working at health stations, secondary data, human resource reports; training reports. The research results show that Luc Nam Health Center in the period of 2021-2022 lacks human resources compared to the job position. Of which, the most lacking are general practitioners. The human resource structure is not reasonable according to the job position, there is a lack of Traditional Medicine and Public Health doctors. Regarding the quality of human resources, at health stations, there are no staff trained after university. Conclusion: Luc Ngan Health Center lacks medical staff resources in both quantity and professional structure according to the job position.